Transformation of Emergency & Trauma Department in Response to COVID-19 Pandemic - Mohd Zaini, Nurul Nasibah; Anuar, Azmir; Mun, Chung Wai (International Journal of Human and Health Sciences (IJHHS), 2023)
Objectives: COVID-19 pandemic has caused tremendous impact on Emergency & Trauma Department (ETD) worldwide including ETD Hospital Taiping (HTPG). It is a large department with approximately 200 staff and a daily admission load that achieves an average of 250-300 patients per day, with an expected load increment during festivals and weekends. This article illustrates reorganizing strategies of ETD HTPG in setting up system and rules implementation in response to COVID-19 pandemic since the year 2020. Methods: This is a descriptive report on the transformation of dedicated facilities to cope with COVID-19 pandemic since the year 2020. Plan-DO-Check-Act (PDCA) has been implemented to improve the systems. The report is written based on the actual clinical needs, development and advancement of emergency medical services in ETD HTPG. Results: Elimination of COVID-19 pandemic virus is impossible in the near future in a start year of 2020. Isolation has turned out to be the next crucial step in controlling the pandemic. The creation of Triage Isolation Booth (TIB) has reduced transmission risks while allowing staff to carry out their usual triage process. Three emergent clinical areas were formed in an ad-hoc manner to cater to the pandemic, namely Respiratory Zone, Influenza-Like Illness (ILI) & COVID Zone in addition to basic 3 zones of red, yellow and green. New norms, rules and regulations are adapted to all ETD staff, patients and visitors. Conclusion: This article is meant to share our initiative and strategies in handling and managing COVID-19 cases with multiple challenges and limitations of resources in ETD HTPG. As a point of success of these strategies, we have recorded only 3 isolated positive cases among ETD staff in the year 2020. To date, the system is being practiced and revised from time to time to achieve better performance for patients’ needs. International Journal of Human and Health Sciences Supplementary Issue: 2023 Page: S21